2021
DOI: 10.1002/ldr.4045
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of damaged ecosystems in desert steppe open‐pit coal mines: Effects on soil nematode communities and functions

Abstract: Repair of damaged areas in open-pit (opencast) coal mines has emerged as an important environmental concern. Our research investigated the mechanism by which different ecological restoration methods affected soil nematode communities in damaged areas of desert steppe coal mines. Using high-throughput sequencing technology, nematode community composition, diversity, and function were analyzed to determine the response of nematodes to different ecological restoration methods in damaged areas of coal mines. For s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…This was also consistent with our hypothesis that ecological package restoration can be beneficial to the restoration of nematode communities. At the same time, combined with our previous research findings(Han et al, 2021), we recommend using ecological package restoration and alien soil restoration to carry out ecological restoration of open-pit mine wasteland.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…This was also consistent with our hypothesis that ecological package restoration can be beneficial to the restoration of nematode communities. At the same time, combined with our previous research findings(Han et al, 2021), we recommend using ecological package restoration and alien soil restoration to carry out ecological restoration of open-pit mine wasteland.…”
mentioning
confidence: 59%
“…At the same time, the results of the fauna analysis suggested that the nutrient status of the Ba treatment soil was good, and associated with a lower disturbance intensity and a relatively stable food web. Similarly, from the correlation between genera (Figure S6), it can be seen that, compared to the other treatments, the soil nematode community under the Ba treatment was more complex and the proportion of positive correlations between genera was larger (Han et al, 2021). The goal of effective ecological restoration is that the ecosystem has homeostasis post restoration (Dunger et al, 2001; Gatica‐Saavedra et al, 2017), eventually reaching the same state as the original ecosystem (i.e., a complete return to the conditions of the pre‐disturbed ecosystem ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We used internationally accepted methods to measure soil pH, organic matter, ammonium nitrogen (ammonium root‐N), nitrate nitrogen (nitrate‐N), available phosphorus (AP), available potassium (AK), total nitrogen (TN), and moisture content (Han et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The total DNA content present in the soil samples was extracted following the instructions of the EZNA soil kit (Omega Bio-Tek, Norcross, GA, USA). The sequences D2A 5 0 -ACAAGTACCGTGAGGGAAAGT-3 0 and D3B 5 0 -TGCGAAGGAACCAGCTACTA-3 0 were used for amplification of the 28S rDNA highly conserved region (Gao et al, 2022;Han et al, 2021;Nunn, 1992). The Shanghai Meiji Biomedical Technology Co., Ltd. performed the sequencing using the MiSeq PE300 platform (Illumina).…”
Section: High-throughput Sequencingmentioning
confidence: 99%